Severity of native pulmonary annular hypoplasia and late outcomes of tetralogy of Fallot: retrospective cohort study (Swiss Medical Weekly, 2024)
OBJECTIVE: Pulmonary annular hypoplasia and valvar dysplasia are key morphological features affecting long-term outcomes of tetralogy of Fallot. This retrospective study aimed to analyse factors affecting contemporary long-term outcomes with a focus on pulmonary annular growth and function over time.METHODS: 131 consecutive isolated tetralogy of Fallot repairs performed between 2004 and 2014 at University Children’s Hospital Zurich were included. Median age and weight at the time of repair were 4.8 (interquartile range [IQR] 3.2–6.3) months and 6.1 (IQR 5.1–7) kg, respectively. Based on the severity of native pulmonary annular hypoplasia, the cohort was divided into group 1 (preoperative pulmonary annular Z score < –4; n = 20), group 2 (Z score –2 to –4; n = 56) and group 3 (Z score > –2; n = 54). A transannular patch was used in 88/131 (67.2%) patients: 80%, 67.9% and 61.1% in groups 1, 2 and 3, respectively. The primary outcome was defined as right ventricular outflow tract (RVOT) reoperation or pulmonary valve replacement. Secondary outcome was composite pulmonary valve dysfunction defined as peak gradient >40 mm Hg or severe pulmonary regurgitation at follow-up. A multiple Cox regression model was used to quantify the association of age at tetralogy of Fallot repair, preoperative pulmonary annular Z score and RVOT approach with primary and secondary outcome. Follow-up was 98.5% complete, with a median follow-up duration of 9.6 (95% confidence interval [CI] 9–10.4) years.RESULTS: All patients were alive at last follow-up resulting in 100% survival. 20/131 patients underwent pulmonary valve replacement (14 surgical and 6 catheter interventional) while 5/131 underwent RVOT reoperations other than valve replacement. The Kaplan-Meier 10-year freedom from primary outcome was 85% (95% CI 78–92%); 69% (46–100%), 91% (82–100%) and 84% (74–95%) for groups 1, 2 and 3, respectively (log rank p = 0.16). Composite dysfunction at follow-up was observed in 29.8% (overall): 45%, 28.6% and 25.9% for groups 1, 2 and 3, respectively (p = 0.12). The multiple Cox regression analysis for primary outcome indicated that the use of a transannular patch results in a Hazard Ratio (HR) of 3.3 (95% CI 0.7–14.7, p = 0.13). Additionally, the presence of composite dysfunction at discharge results in a HR of 2.1 (95% CI 0.8–5.4, p = 0.1). Age (in months) with a HR of 0.8 (95% CI 0.6–1, p = 0.06) and group 2 with a HR of 0.4 (95% CI 0.14–1.2, p = 0.11) showed a trend to being protective for the primary outcome. However, the 95% CI of all estimates included the HR of 1.CONCLUSIONS: Transannular patch use and composite dysfunction at discharge, although not statistically significant at 5% level, may be associated with pulmonary valve replacement and RVOT reoperation. Avoiding the use of a transannular patch or using reconstructive techniques to achieve a better composite dysfunction at discharge could reduce the primary outcome. Large multicentre studies are needed to demonstrate more precisely the impact of pulmonary annulus Z scores on outcome.